Pait Village towards Smart Village with Creation and Support of Village Websites for Public Accountability - Izzalqurny, Tomy Rizky; Sanputra, Adrian Hartanto Darma; Ferdiansyah, Rifaldy Adinandra (Jurnal Pengabdian Masyarakat, 2025)
Purpose: Community service This aims For develop the Pait Village website as part from effort towards a smart village which aims increase transparency information population and accountability public. The problem faced is lack of access to information village consequence loss of previous website. Method: Method used in study This covers observation live, discussion group Focus Group Discussion, development website, as well as socialization and training to apparatus village. Data collected through surveys and questionnaires distributed to device village and community. Practical Application: Research results This potential repair transparency government village and make it easier access information for public through digital platforms. This website can also be used for the promotion of tourist village and improve the growth of local economy. Conclusion: Website development successfully increases access to information and skill tools for village management in the digital system. This program shows a positive impact on transparency and effective public service in Pait Village.